Increasing Vase Life of Cut Gerbera cv. Rosalin Flowers Using Nanocomposites as Preservative Solution - Simin Garavand; S.F. Mousavi; S.H. Hekmatara (Majallah-i ̒Ulum-i Bāghbānī, 2023)
Introduction Gerbera is one of the most important cut flowers that has a short vase life. Like other cut flowers, one of the main concerns after harvesting this flower is reducing its quality. The application of carbon nanotubes as preservative solutions increase water uptake, balances water relations, and increases the vase life of cut flowers. Agglomeration, lack of proper dispersion, and severe hydrophobicity are the disadvantages of carbon nanotubes that prevent optimal dispersion in the solution. In this study, polymers (polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), and non-ionic surfactant Triton X-100) were used to increase the dispersion of multiwalled carbon nanotubes (MWCNTs). Their effect on the longevity of cut gerbera flowers was also investigated. Materials and Methods The experiment was performed as a factorial experiment in a completely randomized design with four replications. Gerbera (Gerbera jamesonii cv. Rosalin) flowers with fully opened ray florets were purchased. During transportation, each cut flower was covered individually with a cellophane sheet and was placed inside a box of paper to minimize water loss. Gerbera stems were placed in a vase solution as pulse treatment for 24h. Treatments included various concentrations of nanocomposite including control (distilled water), MWCNTs-PVP nanocomposite (1 and 2 mg L-1), MWCNTs-PEG nanocomposite (1 and 2 mg L-1), and MWCNTs-Triton X-100 nanocomposite (1 and 2 mg L-1). Distilled water was used for the control treatment. After the cut gerbera flowers underwent pulse treatment, they were placed individually into glass vases filled with distilled water. Throughout the experiment, the vase life, relative fresh weight, water uptake, relative water content of petals and stems, as well as the bacterial population at the end of the stem were measured. Results and Discussion The study showed that the MWCNTs-Triton X-100 with a concentration of 2 mg L-1 provided the longest vase life of cut flowers, with a duration of 22.5 days, which was an 8-day increase compared to the control. The other nanocomposites (MWCNTs-PVP and MWCNTs-PEG) also improved the longevity of the cut flowers compared to the control. The nanocomposites in the vase solution affected the relative fresh weight and water uptake of the cut stems. The study found that the water uptake pattern was similar to the fresh weight of the flower, and the water uptake capacity of the stem gradually decreased with time. The MWCNTs-Triton X-100 with a concentration of 1 mg L-1 resulted in the highest amount of water uptake. Cut flowers pulsed with this concentration exhibited the highest relative water content in both petals and stems. The application of MWCNTs-PEG nanocomposite (1 mg L-1) in vase solution increased the relative fresh weight of gerbera cut flowers. Our findings suggest that MWCNTs can increase water uptake, resulting in increased fresh weight in the cut stem. SEM analysis revealed that after the evaluation period, MWCNTs were detected in the stem of cut gerbera and deposited on the stem's internal surface. Our finding showed that the bacterial population at the end of the stem in control treatment during the vase life period was higher than the bacterial population at the end of the stem of flowers treated with MWCNTs-Triton X-100 treatment (2 mg L-1). Therefore, reducing bacterial blockages in the xylem vessels improves the water uptake and vase life of cut flowers. Conclusion When gerbera cut flowers are harvested and kept in vase solutions, they face some challenges including wounding and water stress. Continuity of water flow in cut flower stem after cutting is an important factor in determining postharvest quality and longevity of cut flowers. Applying a solution containing well-dispersed MWCNTs is a novel approach for facilitating the entry of this nanotube into plants. The use of a composite of MWCNTs with X-100, PVP, and PEG exhibits excellent dispersion properties in the aqueous media of vase solution. These nanocomposites were successful compounds in increasing water uptake, maintaining fresh weight, and increasing the vase life of gerbera cut flowers. The findings of the present study showed that nanocomposites inhibit bacterial growth. These results suggest that the elimination of barriers to water flow in the cut stem helps to keep the longevity and delayed senescence.